[Literature of the supernatural worlds beyond reason] (The Center [producer], 1960)
Explores some of our questions and feelings about the mysterious, nonrational aspects of the universe. The literary works examine the human desire for knowledge and power that transcends the boundaries of time, space, reason and life itself.